2012
DOI: 10.4028/www.scientific.net/amm.190-191.1238
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fractal Theory in the River Regime in the Lower Yellow River

Abstract: From 1960 to 1999, the river regime in the Lower Yellow River had been the wandering. After the operation of Xiaolangdi Reservoir, the river regime in the Lower Yellow River has experienced some changes because of the reduced discharge and sediment loads. According to the river regime maps, the wandering features of the Lower Yellow River are inhibited and the river channel is becoming stable. In addition, the fractal dimension method is introduced to discriminate the river regime. The river fractal features a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Based on the previous literature, we found that the capacity dimensions of river networks ranged from 1.83 to 1.93 in mountainous areas [4,5,53,54], while in low mountainous areas the capacity dimensions of river networks ranged from 1.49 to 1.81 [19,20,54]. Besides this, the capacity dimensions of river networks in the Lower Yellow River were found to range from 1.10 to 1.18 [55], and then weakened dramatically to 1.05-1.35, due to the influence of the Xiaolangdi Reservoir [56].…”
Section: Multifractal Analysis Of River Network From Other Areasmentioning
confidence: 90%
“…Based on the previous literature, we found that the capacity dimensions of river networks ranged from 1.83 to 1.93 in mountainous areas [4,5,53,54], while in low mountainous areas the capacity dimensions of river networks ranged from 1.49 to 1.81 [19,20,54]. Besides this, the capacity dimensions of river networks in the Lower Yellow River were found to range from 1.10 to 1.18 [55], and then weakened dramatically to 1.05-1.35, due to the influence of the Xiaolangdi Reservoir [56].…”
Section: Multifractal Analysis Of River Network From Other Areasmentioning
confidence: 90%
“…Yu et al (2011) took Bengbu to Fushan reach as an example, and analysed the incoming water and sediment, bed-building discharge, and riverbed stability coefficient. For other rivers, Tian et al (2012) used the fractal theory to analyse the evolution of the lower Yellow River. Batalla et al (2018) studied the morphology of theÑuble River channel changing over the years based on aviation images, and quantitatively analysed the channel morphology index.…”
Section: Introductionmentioning
confidence: 99%
“…Because of flood season randomness, certainty, and fuzziness, the flood season division method is varied according to its characteristics. The current flood season staging methods mainly include the change point analysis method [14], fuzzy set analysis method [15], system clustering method [16], and Fisher most segmentation method [17]. These methods have shortcomings, such as single selection index or cumbersome calculation.…”
Section: Introductionmentioning
confidence: 99%